The Paradigm of Hadith Transmission Bi al-Maʿna: Reinterpretation and Infiltration in the Hadiths on Ablution and Zakat: Paradigma Periwayatan Hadis Bi Al-Ma’na: Upaya Reinterpretasi dan Infiltrasi Hadis Perintah Berwudhu dan Membayar Zakat - Alif Hibatullah; Afro' Anzalina Nurizzati Arifah; Rif’iyatul Fahimah; Burhan Djamaluddin (Takwil: Journal of Quran and Hadith Studies, 2026)
This study aims to examine whether textual variations resulting from transmission bi al-maʿna should be understood as legitimate forms of interpretation or rather as instances of semantic infiltration into the hadith. Narration of hadith bi al-maʿna (transmission according to meaning) is one of the methods of hadith transmission that has long been debated among hadith scholars because of its potential to generate textual variations in the matn (text) of hadith. On the one hand, this method aims to preserve the substantive meaning of a hadith when its original wording cannot be recalled accurately. On the other hand, transmission bi al-maʿna also creates the possibility of semantic shifts and even textual interpolation within the hadith text. This study adopts a qualitative descriptive design employing matn criticism as its primary analytical approach. The analysis involves a comparative examination of parallel narrations, an assessment of potential semantic shifts, the identification of possible idraj (interpolation), and an evaluation of the narrations in light of the general principles of Islamic law. The study focuses on the hadith concerning the obligation to pay zakat al-fitr and the hadith instructing Muslims to complete the ablution (wuduʾ) properly. The findings indicate that the textual variation found in the hadith on zakat al-fitr falls within the category of ziyadat al-thiqah (addition by a trustworthy transmitter), which does not alter the substantive meaning of the narration and can therefore be regarded as a legitimate interpretive variation. In contrast, the hadith concerning the completion of ablution exhibits indications of idraj, suggesting the possibility of semantic infiltration resulting from the incorporation of a Companion's statement into the matn. Accordingly, matn criticism plays a crucial role in distinguishing between textual variations that constitute legitimate interpretive developments and those that potentially represent semantic infiltration in the transmission of hadith bi al-maʿna.